Colocación de implantes dentales en maxilar atrófico con técnica de cresta dividida y expansión del reborde - Reyes Doimi, Juan (2017)
ABSTRACT: The present case report describes placement of tooth implants in a patient with history of smoking, exhibiting severe, chronic periodontitis and maxillary atrophy with horizontal bone volume deficiency. Simultaneously to implant placement, the technique of divided crest, ridge expansion and bovine bone graft placement was used. After six months, bone integration of all implants was observed and a hybrid, implant-supported prosthesis was manufactured (full bone anchorage). Finally the case was followed for 18 months without observing any complications, and with satisfactory functional and esthetic results for the patient.